DeepCAS: A Deep Reinforcement Learning Algorithm for Control-Aware Scheduling - Demirel, B.; Ramaswamy, A.; Quevedo, D. E.; Karl, H. (IEEE Contr. Syst. Lett.)

Transmission scheduling for remote state estimation and control with an energy harvesting sensor - Leong, A.; Dey, S.; Quevedo, D. E. (Automatica)

Event-Triggered Quantized Communication-Based Distributed Convex Optimization - Liu, S.; Xie, L.; Quevedo, D. E. (Trans. Contr. Network Syst.)

On Efficiently Solvable Cases of Quantum k-SAT - Aldi, Marco; de Beaudrap, Niel; Gharibian, Sevag; Saeedi, Seyran (43rd International Symposium on Mathematical Foundations of Computer Science (MFCS 2018))
The constraint satisfaction problems k-SAT and Quantum k-SAT (k-QSAT) are canonical NP-complete and QMA_1-complete problems (for k >= 3), respectively, where QMA_1 is a quantum generalization of NP with one-sided error. Whereas k-SAT has been well-studied for special tractable cases, as well as from a parameterized complexity perspective, much less is known in similar settings for k-QSAT. Here, we study the open problem of computing satisfying assignments to k-QSAT instances which have a "matching" or "dimer covering"; this is an NP problem whose decision variant is trivial, but whose search complexity remains open. Our results fall into three directions, all of which relate to the "matching" setting: (1) We give a polynomial-time classical algorithm for k-QSAT when all qubits occur in at most two clauses. (2) We give a parameterized algorithm for k-QSAT instances from a certain non-trivial class, which allows us to obtain exponential speedups over brute force methods in some cases by reducing the problem to solving for a single root of a single univariate polynomial. (3) We conduct a structural graph theoretic study of 3-QSAT interaction graphs which have a "matching". We remark that the results of (2), in particular, introduce a number of new tools to the study of Quantum SAT, including graph theoretic concepts such as transfer filtrations and blow-ups from algebraic geometry; we hope these prove useful elsewhere.
Keywords: search complexity; local Hamiltonian; Quantum SAT; algebraic geometry

Quantum Generalizations of the Polynomial Hierarchy with Applications to QMA(2) - Gharibian, Sevag; Santha, Miklos; Sikora, Jamie; Sundaram, Aarthi; Yirka, Justin (43rd International Symposium on Mathematical Foundations of Computer Science (MFCS 2018))
The polynomial-time hierarchy (PH) has proven to be a powerful tool for providing separations in computational complexity theory (modulo standard conjectures such as PH does not collapse). Here, we study whether two quantum generalizations of PH can similarly prove separations in the quantum setting. The first generalization, QCPH, uses classical proofs, and the second, QPH, uses quantum proofs. For the former, we show quantum variants of the Karp-Lipton theorem and Toda's theorem. For the latter, we place its third level, Q Sigma_3, into NEXP using the Ellipsoid Method for efficiently solving semidefinite programs. These results yield two implications for QMA(2), the variant of Quantum Merlin-Arthur (QMA) with two unentangled proofs, a complexity class whose characterization has proven difficult. First, if QCPH=QPH (i.e., alternating quantifiers are sufficiently powerful so as to make classical and quantum proofs "equivalent"), then QMA(2) is in the Counting Hierarchy (specifically, in P^{PP^{PP}}). Second, unless QMA(2)= Q Sigma_3 (i.e., alternating quantifiers do not help in the presence of "unentanglement"), QMA(2) is strictly contained in NEXP.
Keywords: Complexity Theory; Quantum Computing; Polynomial Hierarchy; Semidefinite Programming; QMA(2); Quantum Complexity

The Complexity of Simulating Local Measurements on Quantum Systems - Gharibian, Sevag; Yirka, Justin (12th Conference on the Theory of Quantum Computation, Communication and Cryptography (TQC 2017))
An important task in quantum physics is the estimation of local quantities for ground states of local Hamiltonians. Recently, Ambainis defined the complexity class P^QMA[log], and motivated its study by showing that the physical task of estimating the expectation value of a local observable against the ground state of a local Hamiltonian is P^QMA[log]-complete. In this paper, we continue the study of P^QMA[log], obtaining the following results. The P^QMA[log]-completeness result of Ambainis requires O(log n)-local observ- ables and Hamiltonians. We show that simulating even a single qubit measurement on ground states of 5-local Hamiltonians is P^QMA[log]-complete, resolving an open question of Ambainis. We formalize the complexity theoretic study of estimating two-point correlation functions against ground states, and show that this task is similarly P^QMA[log]-complete. P^QMA[log] is thought of as "slightly harder" than QMA. We justify this formally by exploiting the hierarchical voting technique of Beigel, Hemachandra, and Wechsung to show P^QMA[log] \subseteq PP. This improves the containment QMA \subseteq PP from Kitaev and Watrous. A central theme of this work is the subtlety involved in the study of oracle classes in which the oracle solves a promise problem. In this vein, we identify a flaw in Ambainis' prior work regarding a P^UQMA[log]-hardness proof for estimating spectral gaps of local Hamiltonians. By introducing a "query validation" technique, we build on his prior work to obtain P^UQMA[log]-hardness for estimating spectral gaps under polynomial-time Turing reductions.
Keywords: Complexity theory; Quantum Merlin Arthur (QMA); local Hamiltonian; local measurement; spectral gap

Ground State Connectivity of Local Hamiltonians - Gharibian, Sevag; Sikora, Jamie (ACM Transactions on Computation Theory (TOCT))
Keywords: Local Hamiltonian; ground state connectivity; quantum Hamiltonian complexity; reconfiguration problem

Computing subfields of number fields and applications to Galois group computations - Elsenhans, Andreas-Stephan; Klüners, Jürgen (Journal of Symbolic Computation)
A polynomial time algorithm to find generators of the lattice of all subfields of a given number field was given in van Hoeij et al. (2013). This article reports on a massive speedup of this algorithm. This is primary achieved by our new concept of Galois-generating subfields. In general this is a very small set of subfields that determine all other subfields in a group-theoretic way. We compute them by targeted calls to the method from van Hoeij et al. (2013). For an early termination of these calls, we give a list of criteria that imply that further calls will not result in additional subfields. Finally, we explain how we use subfields to get a good starting group for the computation of Galois groups.
Keywords: Computational Mathematics; Algebra and Number Theory

Silizium-Halbleitertechnologie - Hilleringmann, Ulrich

Ätztechnik - Hilleringmann, Ulrich (Silizium-Halbleitertechnologie)

Time domain electrical characterization in zinc oxide nanoparticle thin-film transistors - Becker, Thales E.; Vidor, Fabio F.; Wirth, Gilson I.; Meyers, Thorsten; Reker, Julia; Hilleringmann, Ulrich (2018 IEEE 19th Latin-American Test Symposium (LATS))

Time domain electrical characterization in zinc oxide nanoparticle thin-film transistors - Becker, Thales E.; Vidor, Fabio F.; Wirth, Gilson I.; Meyers, Thorsten; Reker, Julia; Hilleringmann, Ulrich (2018 IEEE 19th Latin-American Test Symposium (LATS))

Oxidation des Siliziums - Hilleringmann, Ulrich (Silizium-Halbleitertechnologie)

One Class Genera of Lattice Chains Over Number Fields - Kirschmer, Markus; Nebe, Gabriele (Algorithmic and Experimental Methods in Algebra, Geometry, and Number Theory)
We classify all one-class genera of admissible lattice chains of length at least 2 in hermitian spaces over number fields. If L is a lattice in the chain and p the prime ideal dividing the index of the lattices in the chain, then the {p}-arithmetic group Aut(Lp) acts chamber transitively on the corresponding Bruhat-Tits building. So our classification provides a step forward to a complete classification of these chamber transitive groups which has been announced 1987 (without a detailed proof) by Kantor, Liebler and Tits. In fact we find all their groups over number fields and one additional building with a discrete chamber transitive group.

One-class genera of exceptional groups over number fields - Kirschmer, Markus (Journal de Théorie des Nombres de Bordeaux)
We show that exceptional algebraic groups over number fields do not admit one-class genera of parahoric groups, except in the case G₂ . For the group G₂, we enumerate all such one-class genera for the usual seven-dimensional representation.
Keywords: Algebra and Number Theory

Liquid crystalline dithienothiophene derivatives for organic electronics - Vollbrecht, Joachim; Oechsle, Peter; Stepen, Arne; Hoffmann, Florian; Paradies, Jan; Meyers, Thorsten; Hilleringmann, Ulrich; Schmidtke, Jürgen; Kitzerow, Heinz (Organic Electronics)
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Condensed Matter Physics; General Chemistry; Biomaterials; Electronic; Optical and Magnetic Materials

Torsion free sheaves on Weierstraß cubic curves and the classical Yang-Baxter equation - Burban, Igor; Galinat, L. (Communications in Mathematical Physics)
This work deals with an algebro–geometric theory of solutions of the classical Yang–Baxter equation based on torsion free coherent sheaves of Lie algebras on Weierstraß cubic curves.

Non-commutative nodal curves and derived tame algebras - Burban, Igor; Drozd, Yu.

Fourier-Mukai transform on Weierstraß cubics and commuting differential operators - Burban, Igor; Zheglov, A. (International Journal of Mathematics)

Photovoltaic yield prediction using an irradiance forecast model based on multiple neural networks - Durrani, Saad Parvaiz; Balluff, Stefan; Wurzer, Lukas; Krauter, Stefan (Journal of Modern Power Systems and Clean Energy)